Radiological and pathological diagnosis of paediatric bone tumours and tumour-like lesions. - Vlychou, M; Athanasou, N (2008)
Primary bone tumours are rare but account for a significant proportion of cancers occurring in childhood and adolescence. Malignant bone tumours need to be distinguished not only from their benign counterparts but also from tumour-like lesions, many of which are developmental or reactive in nature and are found commonly in the paediatric population. Taking note of the age of the patient and the site of the lesion within bone (aided by several imaging techniques including plain radiographs, ultrasound, computed tomography, bone scintigraphy and magnetic resonance imaging) is essential for pathological diagnosis. Immunohistochemistry, cytogenetics, molecular analysis and other techniques are now powerful diagnostic tools in bone pathology. This review aims to provide an approach to the radiological and pathological diagnosis of paediatric bone tumours. It also provides a brief overview of some of the more common bone tumours and tumour-like lesions, both benign and malignant, which occur in childhood and adolescence.